Evaluation of Information Security Management Based on ISO/IEC 27001 at Universitas Nasional Library (UNAS) - fadilah, Afifah Nur; Saputra, Dwi Fajar; Fyras Maulana, Ibnu; Jordan A. N, Muhammad; Rizky Jumayyil, Dzaki; T. M., Sarah Aurelia; Mufiddah Adhayanti, Saffana (Jurnal Tadwin, 2025)
As the utilization of digital systems continues to grow, libraries must strengthen their information management systems to protect against threats such as cyberattacks and data breaches. This study employed a descriptive qualitative approach using interviews, observation, and documentation. The findings indicate that several ISO/IEC 27001 based controls have been implemented, including firewalls, encryption, and regular audits. However, security gaps remain, such as weak credentials, the absence of multi-factor authentication, and limited real-time monitoring and data backup. Major risks include malware, network attacks, and system failures. Although the National University (UNAS) Cyber Library has developed a Disaster Recovery Plan (DRP), improvements in formal documentation and user digital literacy are still needed. These findings serve as a strategic evaluation basis for enhancing the effectiveness of information security governance in academic library environments.